Legal Aspects in Determining Floods as a National Disaster - Abdul Kahar Maranjaya; Sodikin Sodikin (JURNAL AKTA, 2026)
The flash floods that struck West Sumatra, North Sumatra, and Aceh in late 2025 resulted in environmental damage and numerous deaths. Community groups have demanded that the government immediately declare the disaster a national disaster. This study employed a descriptive normative method with a qualitative analysis model. The findings explain the legal aspects of disaster management as stipulated in Law Number 24 of 2007, along with its implementing regulations. This law establishes criteria for determining the legal status of a disaster. The regulation stipulates that the legal status of a disaster is determined by whether it qualifies as a national disaster. If the disaster is local in nature, the local government has the authority and responsibility to manage the situation at the regional level. In addition, based on Law Number 24 of 2007 concerning Disaster Management, the President will only fully declare a national disaster if the regional government is completely paralyzed and no longer able to manage resources.